Kegiatan literasi untuk anak-anak di Dusun Brengosan Donoharjo Ngaglik Sleman Yogyakarta - Prayogo, Muhaimi Mughni; Wardani, Wardani (Buletin Pengabdian Multidisiplin, 2023)
Purpose − This activity aims to help elementary school-age children in Dusun Brengosan Donoharjo Sleman Yogyakarta who have problems with reading. For some children, online learning and periodic assignments made by the school are difficult to follow. The impact of this learning is that there are some children who do not master early reading and comprehension of reading content. Method − The method of this service activity is tutorial. Participants consisted of 7 children consisting of 2 children in grade 1 SD, 1 child in grade 3, 3 children in grade 4, and 1 child in grade 5. This activity is carried out every Sunday for 2 consecutive weeks . The first week is an assessment of all children's reading abilities (5-6 December 2021). Second week (December 12-13 2021), reading skill tutorial activities. Findings − The result of this activity is the increasing ability of 1st and 5th graders to distinguish similar letters. For grades 3 and 4, they understand the core concepts of the reading and can retell it in their own language. Children participating in literacy activities also showed high motivation in participating in activities from start to finish in all sessions. Parents and children expressed that they wanted this activity to continue. This activity is a supporting activity for the village program in the form of village literacy which is funded by a combination of funding sources from Tamanssiwa's Bachelor of Science University and Mitra Kas.